Front Cover: Productivity of a preparative high‐performance liquid chromatography isolation of anacardic acids from cashew nut shell liquid. Issue 6 (11th June 2019) - Oiram Filho, Francisco; Zocolo, Guilherme J.; Canuto, Kirley M.; Silva Junior, Ivanildo J. da; de Brito, Edy S.
Abstract : DOI:10.1002/sscp.201900014 The cover picture shows the anacardic acids isolation. Anacardic acids are alkyl phenols, with biological activities, obtained as a byproduct from cashew nut processing, namely the cashew nut shell liquid. As many natural products its commercial availability is restricted. Therefore, anacardic acids isolation by preparative reversed phase HPLC was developed. The yield, recovery, purity, solvent consumption and productivity were analyzed. The preparative HPLC isolation lead to a productivity of 0.681 Kg.day −1 .Kg −1 of anacardic acids with purity of 96.41, 95.32 and 90.77% for anacardic acid triene, diene and monoene, respectively.